Implementasi Metode Muhadatsah dalam Meningkatkan Kompetensi Dialogis Santri Di Pesantren Al Madina Prabumulih - HIdayatullah; M Jadid Khadavi; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
Arabic language learning in Islamic boarding schools plays a strategic role in supporting the understanding of Islamic sciences, particularly fiqh. However, in practice, Arabic instruction tends to emphasize grammatical aspects, while students’ speaking skills and dialogical competence remain underdeveloped. This condition is also found at Al Madina Islamic Boarding School in Prabumulih, where students experience difficulties in conducting dialogues in Arabic within the context of fiqh learning. Therefore, it is necessary to implement communicative learning methods, one of which is the muhadatsah method. This study aims to describe the implementation of the muhadatsah method in Arabic language learning and to analyze its contribution to improving students’ dialogical competence in fiqh lessons at Al Madina Islamic Boarding School, Prabumulih. This research employs a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation, involving Arabic language teachers, fiqh teachers, and students as research participants. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of the muhadatsah method improves students’ dialogical competence, as reflected in increased confidence, fluency, and accuracy in using Arabic during fiqh-related dialogues. The teacher’s role as a facilitator and motivator, along with the use of contextual fiqh-based dialogue themes, constitutes a key factor in the success of this method. Nevertheless, several challenges remain, including limited instructional time and differences in students’ language proficiency. This study implies that the systematic and sustainable application of the muhadatsah method is essential as a communicative learning strategy to enhance the quality of Arabic and fiqh instruction in Islamic boarding schools.